Incidental abnormal ECG findings and long-term cardiovascular morbidity and all-cause mortality: A population based prospective study. (15th November 2019) - Goldman, Adam; Hod, Hanoch; Chetrit, Angela; Dankner, Rachel
Abstract: Background: The additional prognostic value of resting electrocardiogram (ECG) in long-term cardiovascular disease (CVD)-risk-assessment is unclear. We evaluated the association of incidental abnormal ECG findings with long-term CVD-risk and all-cause mortality, and assessed the additional prognostic value of ECG as a screening tool in adults without known CVD. Methods: A cohort of 2601 Israeli men and women without known CVD were actively followed from 1976 to 1982 for 23-year cumulative CVD-incidence, and until May 2017 for all-cause mortality. At baseline and follow-up, participants underwent interviews, physical examinations, blood tests and ECG. Results: At baseline, 1199 (46.1%) had incidental abnormal ECG findings (exposed-group). CVD cumulative incidence reached 31.6% among the 930 survivors who participated in the active follow-up (294/930). During a 31-year median follow-up, 1719 (66.1%) of the total cohort died. Incidental abnormal ECG findings were associated with 46% greater CVD-risk (odds ratio = 1.46, 95%CI = 1.09–1.97). The net reclassification improvement (NRI) of CVD-risk was 7.4% (95%CINRI  = 1.5%–13.3%, p  = 0.01) following the addition of ECG findings, but the C-index improvement was not statistically significant [C-index = 0.656 (0.619–0.694) vs. C-index = 0.666 (0.629–0.703), p  = 0.14]. Multivariable Cox regression demonstrated an all-cause mortality hazard ratio (HR) of 1.18 (95%CI = 1.07–1.30) for exposed vs. unexposed individuals. Non-specific T-wave changes and left-axis deviation are the incidental ECG abnormalities that were associated with all-cause mortality [HR = 1.18 (95%CI = 1.05–1.33) and HR = 1.19 (95%CI = 1.00–1.42), respectively]. Conclusion: Incidental abnormal ECG findings, mainly non-specific T-wave changes and left-axis deviation, were associated with increased long-term CVD-risk and all-cause mortality among individuals without known CVD, and demonstrated net reclassification improvement for CVD-risk. Highlights: Incidental abnormal ECG findings were associated with mortality and CVD risk. The abnormal ECG findings improved 23-year CVD risk classification of 7.4% adults. Non-specific T-wave changes and left-axis deviation associated with increased mortality risk. Screening ECG in low risk healthy adults may improve CVD risk stratification.